2019
DOI: 10.1002/hbm.24615
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal alterations and functional correlates in adolescents and young adults with congenital heart disease

Abstract: There is a high prevalence of neurodevelopmental impairments in individuals living with congenital heart disease (CHD) and the neural correlates of these impairments are not yet fully understood. Recent studies have shown that hippocampal volume and shape differences may provide unique biomarkers for neurodevelopmental disorders. The hippocampus is vulnerable to early life injury, especially in populations at risk for hypoxemia or hemodynamic instability such as in neonates with CHD. We compared hippocampal gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
31
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 79 publications
6
31
1
1
Order By: Relevance
“…Both left and right hippocampal volumes showed significant associations with worse cognitive scores, including memory, but not with anxiety and depression. Other studies that examined hippocampal volumes showed significant bilateral differences between school‐age children with CHD and controls (Fontes et al., 2019; Latal et al., 2016; Munoz‐Lopez et al., 2017). However, our findings could reflect the evaluation of only the SVHD subgroup compared to studies with mixed types of CHD (Fontes et al., 2019; Latal et al., 2016).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Both left and right hippocampal volumes showed significant associations with worse cognitive scores, including memory, but not with anxiety and depression. Other studies that examined hippocampal volumes showed significant bilateral differences between school‐age children with CHD and controls (Fontes et al., 2019; Latal et al., 2016; Munoz‐Lopez et al., 2017). However, our findings could reflect the evaluation of only the SVHD subgroup compared to studies with mixed types of CHD (Fontes et al., 2019; Latal et al., 2016).…”
Section: Discussionmentioning
confidence: 90%
“…Other studies that examined hippocampal volumes showed significant bilateral differences between school‐age children with CHD and controls (Fontes et al., 2019; Latal et al., 2016; Munoz‐Lopez et al., 2017). However, our findings could reflect the evaluation of only the SVHD subgroup compared to studies with mixed types of CHD (Fontes et al., 2019; Latal et al., 2016). By focusing on this subset with cyanotic CHD and excluding other risk factors, such as premature birth (<37 weeks gestation), previous stroke, cardiac arrest, or the use of ECMO, the present study was able to control for additional factors that may have influenced hippocampal volume (age and TBV).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Functional imaging was used to study brain maturity and injury in neonates with CHD (8,9). For example, magnetic resonance spectroscopy studies showed that neonates with cyanotic CHD exhibit characteristic decreased ratio of Nacteyl-aspartate to choline in the thalamus, basal ganglia, and corticospinal tracts (1).…”
Section: Introductionmentioning
confidence: 99%
“…3 Indeed, it is now understood that brain development within the context of critical CHD (i.e., CHDs requiring intensive surgical intervention(s) to sustain life) is often atypical, with signs of deviation from expected neuronal maturation and volumetric trajectories recognisable as early as the late-second/early-third prenatal trimester [4][5][6][7][8] and evidence of structural, functional, and network topological brain abnormalities documented throughout adolescence and young adulthood. [9][10][11][12][13][14][15][16][17][18][19][20] Children and adolescents with critical CHD are also at heightened risk for a range of neurobehavioural and psychosocial challenges, 21 most notably in executive function. [22][23][24][25] Executive function is an umbrella term, encompassing three core components: inhibitory control, working memory, and cognitive flexibility.…”
mentioning
confidence: 99%